Four weeks of slow-paced breathing: a longitudinal, randomized, placebo-controlled study of the autonomic nervous system - Nicolas Bourdillon; Arnaud Rochat; Vanessa Hoop; Grégoire P. Millet (Current Issues in Sport Science)
Introduction The autonomic nervous system (ANS) relies on two essential feedback loops: respiratory sinus arrythmia (RSA) and arterial baroreflex which are both regulated by a complex interplay of sympathetic and parasympathetic activations. The amplitude of RSA is modified by the respiratory frequency, i.e. an increase in respiratory frequency leads to a progressive decline in RSA as vagal effectors become less able to follow variations at higher frequencies. On the contrary, a reduction in the respiratory frequency can increase RSA. Slow Paced Breathing (SPB) is usually associated with deep changes in thoracic volume which increases the parasympathetic tone, and which has numerous expected beneficial effects on health. However, some studies report little or no effects. The goal of this study was to test a personalized SPB training vs. placebo to help disentangle the effects of SPB from those solely linked to breathing awareness or distraction.